Determinasi Kepatuhan Wajib Pajak Orang Pribadi dengan Sanksi Perpajakan Sebagai Pemoderasi pada KPP Pratama Tampan Pekanbaru - Berliani, Mitha Febri; Putri, Annie Mustika; Sari, Dian Puji Puspita (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the influence of the E-Filling system, the level of tax understanding, and taxpayer awareness on the compliance of individual taxpayers with tax sanctions as a moderating variable at KPP Pratama Tampan Pekanbaru. The sample of this study consists of 100 individual taxpayers registered at KPP Pratama Tampan Pekanbaru in 2022. The results of the study indicate that: (1) The E-Filling system has a significant effect on taxpayer compliance; (2) The level of tax understanding does not have a significant effect on taxpayer compliance; (3) Taxpayer awareness has a significant effect on taxpayer compliance; (4) Simultaneously, the E-Filling system, the level of tax understanding, and taxpayer awareness significantly affect taxpayer compliance, with a contribution of 41.1%; (5) Tax sanctions moderate the influence of the E-Filling system and taxpayer awareness on taxpayer compliance. These findings suggest that the implementation of the E-Filling system, increased taxpayer awareness, and appropriate tax sanctions can enhance the compliance of individual taxpayers. Keywords: E-filling system, tax understanding, taxpayer awareness, sanctions.